Is Aristotle’s cosmos hyperbolic? - Ugaglia, Monica (Educação e Filosofia, 2016)
Summary: Aristotle’s refusal of the actual infinite, in any form, leads him to conceive a universe finite in magnitude, containing a finite multiplicity of things. His strict "immanentism" implies that not only physics but mathematics too must be done in this real universe, without concessions to imagination: in Aristotle’s mathematics there are no sets of actually infinite elements, nor lines of actually infinite length. Even worse, there are not even lines of finite length potentially infinitely extendible, no curves going to the infinite. This notwithstanding, Aristotle explicitly says that his restricted way of understanding the infinite is not a problem for mathematicians. Fortunately, he goes further than the mere statement explaining why mathematicians can do without infinite sets, infinite lines and infinitely extensible ones. Keywords: Aristotle; Infinite; Philosophy of mathematics. O Universo de Aristóteles é hiperbólico? Resumo: A refutação do infinito, em toda a sua amplitude, leva Aristóteles a conceber um universo finito em grandeza e detentor de multiplicidade finita de objetos. A sua concepção estritamente "imanentista" implica que um tal universo finito deva abarcar não só a física, mas também a matemática, sem qualquer concessão à imaginação: na matemática de Aristóteles não há, então, conjuntos de elementos infinitos, nem linhas de comprimento infinito. Mais ainda: nem sequer há linhas infinitamente estendíveis ou curvas que rumam ao infinito. Não obstante isso, Aristóteles afirma que a sua visão restritiva do infinito não é exatamente um problema para os matemáticos, e explica de que modo podem abrir mão de conjuntos infinitos e de linhas infinitamente estendidas. Palavras-chave: Aristóteles; Infinito; Filosofia da matemática. L’Universo di Aristotele è iperbolico? Riassunto: Il rifiuto dell’infinito attuale, in ogni sua forma, porta Aristotele a concepire un universo finito in grandezza, contenente una molteplicità finita di oggetti. La sua concezione strettamente "immanentista" implica inoltre che in un tale universo finito debba essere contenuta non solo la fisica ma anche la matematica, senza alcuna concessione all’immaginazione: nella matematica di Aristotele non ci sono dunque insiemi di infiniti elementi, né linee di lunghezza infinita. Ma non solo: non ci sono nemmeno linee infinitamente estendibili, né curve che vanno all’infinito. Ci² nonostante, Aristotele afferma che la sua visione cosa restritiva dell’infinito non sia un problema per i matematici, e spiega in che modo i matematici possano fare a meno di insiemi infiniti e di linee infinitamente estendibili. Parole chiave: Aristotele; Infinito; Filosofia della matemática. Data de registro: 23/02/2016 Data de aceite: 20/04/2016